Analisis Pengaruh Ukuran Kap, Opini Audit, Ukuran Perusahaan, Dan Profitabilitas Perusahaan Terhadap Auditor Switching(Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2015) - Kristiawan, Agus, Drs. Wahyono, M.A., Akt., CA (2017)
This research aimed to analyze the effect of the size of public accounting firm, audit opinion, firm size and profitability of the company to the auditor switching on manufacturing companies listed in Indonesia Stock Exchange 2010-2015 period. The variables used in this research is the size of public accounting firm, opinion audit, company size, company profitability, and auditor switching. The population of the sample is manufacturing companies listed in Indonesia Stock Exchange 2010-2015 period. Samples were determined using purposive sampling method. The research had 126 samples from 21 companies. Data analysis technique used is the logistic regression analysis. The results of this research indicate that the size of public accounting firm does not affect the auditor switching with a significance level (α) 0.088 > 0.05. Audit opinion affect the auditor switching with a significance level (α) 0.016 < 0.05. Firm size does not affect the auditor switching with a significance level (α) 0.380 > 0.05. The company's profitability does not affect the auditor switching with a significance level (α) 0.919 > 0.05. Keywords: auditor switching, the size of public accounting firm, audit opinion, firm size, company profitability.